Multiaxial compressive strength of hybrid fiber reinforced concrete: A unified empirical model - Li, Jian; Hong, Jian; Liu, Shiyao; Zhou, Yuzai; Meng, Kuan (Frontiers in Materials, 2023)
In engineering design, the strength analysis of concrete structures heavily depends on the compressive strength of HFRC, which also has an impact on the stability and safety of the structure. The objective of this study is to develop a unified empirical model that can quickly estimate the compressive strength of HFRC under multiaxial compression. To measure the multiaxial compressive strength of HFRC, 108 cylindrical specimens and 225 cubic specimens were designed for conventional and true triaxial testing, respectively. Two typical stress paths, i.e., proportional loading and constant restraint loading, were employed to simulate the multiaxial compressive strength of HFRC, and stress ratio- and confinement pressure-dependent formulas were proposed to calculate the strength correspondingly. Based on the validation against the available test results, it has been demonstrated that the empirical model can effectively predict the axial strength of HFRC. The test findings reveal that the constraint pressure considerably affects the compressive strength of concrete, and steel fiber can further improve these capabilities significantly.